1985
DOI: 10.3171/jns.1985.62.1.0059
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular reactivity in patients with ruptured intracranial aneurysms

Abstract: The cerebral vasomotor reactivity to arterial hypotension and hypocapnia was studied in 34 patients between the 3rd and 13th day after rupture of an intracranial saccular aneurysm. Using the intra-arterial xenon-133 injection method, regional cerebral blood flow (rCBF) and cerebral metabolic rate of oxygen (CMRO2) were measured. The intraventricular pressure and cerebrospinal fluid (CSF) lactate and pH levels were determined. The degree of vasospasm was measured on angiograms taken immediately following the rC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
3

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(73 citation statements)
references
References 33 publications
4
66
0
3
Order By: Relevance
“…[17,18] The concept of impaired autoregulation mechanisms on admission in patients who later develop DCI has also been described in other articles. [4,7,9,13,15,19] This study also showed that CTP is a practical and useful tool to compare perfusion on admission and during follow-up in patients with SAH since in 87% of patients a good quality admission and follow-up scan was obtained and no side effects of the CT scanning with contrast occurred. Often, transcranial Doppler (TCD) monitoring is used for follow-up monitoring in patients with SAH for the presence of vasospasm.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…[17,18] The concept of impaired autoregulation mechanisms on admission in patients who later develop DCI has also been described in other articles. [4,7,9,13,15,19] This study also showed that CTP is a practical and useful tool to compare perfusion on admission and during follow-up in patients with SAH since in 87% of patients a good quality admission and follow-up scan was obtained and no side effects of the CT scanning with contrast occurred. Often, transcranial Doppler (TCD) monitoring is used for follow-up monitoring in patients with SAH for the presence of vasospasm.…”
Section: Discussionmentioning
confidence: 56%
“…Whether the perfusion deficit reverses or evolves into infarction depends on the extent of the perfusion deficits and the autoregulation capacity [5,6]. The autoregulation mechanism is reported to be altered or defect in patients who develop DCI [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been described that cerebral autoregulation may become disturbed after subarachnoid hemorrhage (SAH), [1][2][3][4][5][6][7] which has been associated with development of delayed cerebral ischemia (DCI). 1,2,[5][6][7][8][9] The transient hyperemic response test (THRT) is a transcranial Doppler (TCD) based method, which characterizes the changes in cerebral blood flow velocity (FV) after a brief compression of the common carotid artery. It is a recognized and simple method of testing autoregulation in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…42 Reduction of cerebral blood flow by hyperventilation is used to control acute increase of intracranial pressure such as epidural haematoma. Voldby et al 43 studied cerebral vasomotor reactivity to hypocapnia in 34 patients between the 3rd and 13th day after rupture of an intracranial aneurysm and reported that the cerebrovascular response to hyperventilation was generally preserved. Clinical grading of SAH (Hunt and Hess classification) correlates with the disturbance of carbon dioxide reactivity, autoregulation and intraeranial pressure (Table II).…”
Section: Carbon Dioxide Reactivitymentioning
confidence: 99%
“…53 After SAH, cerebral blood flow may be reduced in response to small decreases in blood pressure in patients with cerebral vasospasm. In the first week after SAH, a 10-20% reduction of mean arterial blood pressure using trimetaphan or sodium nitroprusside decreased CBF in patients with angiographic cerebral arterial vasospasm, r~ Using the intraarterial 133Xenon injection method, Voldby et al 43 studied the effects of hypotension on CMRO2, AVDO2, cerebral spinal fluid lactate and intraventricular pressure in 34 patients within first 13 days of SAH. Mean arterial blood pressure was reduced between 10 and 20% for five minutes by/v trimetaphan or sodium nitroprusside.…”
Section: Carbon Dioxide Reactivitymentioning
confidence: 99%